AN ABNORMAL SPECIMEN OF THE INDIAN CARP, LABEO BATA (HAMILTON) - GOSWAMI, S.; GOSWAMI, A.; DASGUPTA, M. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2002)
A specimen of Labeo bata (Ham) with abnormal skull bones is reported for the first time from the New Alluvial Zone of West Bengal.